Digital Personal Branding dalam Membentuk Kredibilitas Content Creator - Yovelin, Very; Paramita, Sinta (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
This research will explore digital personal branding through the social media Instagram @verencialaw. Verencia Law is a fashion, beauty, lifestyle content creator from Tangerang, Indonesia and has more than 70,000 followers. The author wants to explore Verencia Law's digital personal branding and credibility on Instagram. The theory used is Peter Montoya's theory regarding the 8 laws of personal branding and the theory of source credibility. Qualitative research approach, netnographic research method, the research subject is content creator Verencia Law and the research object is digital personal branding on the Instagram account @verencialaw. Methods of data collection using observation, documentation, online data review, and literature studies. Data analysis techniques are data reduction, presentation, and conclusion drawing, and the validity of the data is done by triangulation. The results of this study suggest that Verencia Law fulfills the eight personal branding concepts and fulfills the three components of source credibility. In addition, these two theories are still relevant to use in building digital personal branding and credibility. Penelitian ini akan mengeksplorasi digital personal branding akun media sosial Instagram @verencialaw. Verencia Law merupakan content creator fashion, beauty, lifestyle asal Tangerang, Indonesia, dan memiliki pengikut melebihi 70.000 orang. Penulis ingin mengulik digital personal branding dan kredibilitas Verencia Law di Instagram. Teori yang digunakan adalah teori Peter Montoya mengenai delapan hukum personal branding dan teori kredibilitas sumber. Pendekatan penelitian kualitatif,metode penelitian etnografi, subjek penelitian yaitu content creator Verencia Law dan objek penelitian adalah digital personal branding pada akun Instagram @verencialaw. Metode pengumpulan data menggunakan observasi, dokumentasi, tinjauan data online, dan studi kepustakaan. Teknik analisis data adalah reduksi, penyajian, dan penarik kesimpulan data, serta keabsahan data melalui triangulasi. Hasil penelitian ini mengemukakan bahwa Verencia Law memenuhi delapan konsep personal branding dan memenuhi tiga komponen kredibilitas sumber. Selain itu, kedua teori tersebut masih relevan digunakan dalam membentuk digital personal branding dan kredibilitas.